THE GREENHOUSE EFFECT: CAUSES, ENVIRONMENTAL IMPACTS, AND MITIGATION STRATEGIES - Jamshid Ergashev Kuldoshevich (Bright Mind Publishing, 2025)
The greenhouse effect is a natural phenomenon essential for maintaining Earth's habitable temperature. However, human activities have intensified this effect, leading to global warming and climate change. This article explores the causes of the enhanced greenhouse effect, its impacts on the environment, and potential mitigation strategies. Figures and tables are included to illustrate key concepts and data.